Analisis Topografi dalam Penentuan Jalur Evakuasi Tsunami di Kota Padang - Setyawan, Denny; Basuki, Yudi (Jurnal Pembangunan Wilayah dan Kota, 2021)
As one of the tsunami disaster mitigation efforts, the Padang City Government has made a tsunami evacuation map in 2010. However, information regarding the tsunami hazard zone on the map has not been updated to date. Planning for mitigation activities focuses on the coastal areas on the north to the urban centers of the city of Padang. Hills and rice fields on the coast make access to the movement of evacuation communities in the southern region of the city of Padang to be limited. Based on this background, this study aims to conduct topographic analysis in determining potential tsunami evacuation routes in the southern region of Padang City using quantitative methods through the GIS approach. The analysis carried out was community preparedness analysis, tsunami flooding zone modeling, analysis of the level of danger, vulnerability, and tsunami risk. In the end, based on the results of the analysis carried out the determination of potential shelter locations and potential evacuation routes as a form of direction and recommendations regarding tsunami disaster mitigation activities in Padang City. 53 locations of potential evacuation shelter were proposed with details of 18 locations in Bungus Bay, Kabung District, 9 locations in Lubuk Begalung District, and 26 locations in Padang Selatan District. To support the 53 potential locations of the shelter, a potential evacuation route is planned for 52 evacuation routes using the existing road network and 21 proposed evacuation routes to the nearest hills.